Adductor spasmodic dysphonia - A detailed case report on assessment and management - Sandhya Koteshwara; Divya Vernekar; Surabhi MY (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Spasmodic dysphonia is a neurogenic voice disorder which is characterized by severe and spasmodic problems of vocal fold approximation. Symptoms of the disorder consist of several sensations like strain and strangle which varies from mild to severe. Over the years, there have been several attempts in the line of treatment approaches which helps in voice modification by surgical, pharmacological treatment and voice therapy. In the recent years there are many success stories of patients who have benefitted from pharmacological treatments involving partial and temporary paralysis of muscle fibers within the larynx followed by botulinum injection. This article gives a picture of in depth evaluation of a 68 years old male who was diagnosed as having adductor spasmodic dysphonia. Detailed information regarding characteristics of voice, perceptual evaluation,  acoustic analysis of voice, and medical and surgical management opted by the patient is discussed. Efficacy of voice therapy associated with medical management is explained in this case report. The case report emphasizes on the effectiveness of medical as well as therapeutic treatment required for spasmodic dysphonia as well as multifaceted approach to symptom management.